2017
DOI: 10.1136/bcr-2017-221153
|View full text |Cite
|
Sign up to set email alerts
|

Role of metastasectomy and chemotherapy in carcinoma of uterine cervix

Abstract: Squamous cell carcinoma of uterine cervix is potentially a curable disease; however, many patients treated with definitive chemoradiotherapy develop distant metastases, with few of them having a single metastatic deposit. There are no guidelines for the treatment of patients with oligometastatic cervical cancer.We present a case of a patient with International Federation of Gynecology and Obstetrics (FIGO) Stage IIB squamous cell carcinoma of uterine cervix. She was successfully treated with concurrent chemora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Hou et al reported that 19 patients with one to four pulmonary metastases treated with SBRT achieved a median DFS of 12.7 months and a two-year DFS of 76.8% [15]. In these reports on the treatment of oligometastatic disease, most metastatic sites treated with ablative therapies corresponded to para-aortic, supraclavicular lymph node, or lung disease [10][11][12][13][14][15]. In contrast, reports of mediastinal oligometastases, such as those of our patient cases, are very rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hou et al reported that 19 patients with one to four pulmonary metastases treated with SBRT achieved a median DFS of 12.7 months and a two-year DFS of 76.8% [15]. In these reports on the treatment of oligometastatic disease, most metastatic sites treated with ablative therapies corresponded to para-aortic, supraclavicular lymph node, or lung disease [10][11][12][13][14][15]. In contrast, reports of mediastinal oligometastases, such as those of our patient cases, are very rare.…”
Section: Discussionmentioning
confidence: 99%
“…Yamamoto et al presented the outcomes of 29 women with lung metastases treated with surgery, achieving a five-year disease-free survival (DFS) of 32.9% [ 10 ]. Ali et al reported the case of a woman with lung metastases treated with metastasectomy followed by six cycles of carboplatin and paclitaxel, who was disease-free after five years [ 11 ].…”
Section: Discussionmentioning
confidence: 99%